Goodwill and Criteria for its Recognition in Financial Statements - Bumane, Inga (Ekonomika, 2004)
The article summarises a research on goodwill which is one of the most controversial assets. The research includes a comparison between the descriptions of the economic nature of goodwill and an analysis of various valuation methods and accounting policies. The article discusses the internationally recognised problem that there coexist several accepted methods of accounting for goodwill arising from the acquisition of an enterprise, as a result of which the accountancy data of different enterprises and countries are incomparable.